1991
DOI: 10.1103/physrevlett.67.757
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of the extended Hubbard model in high dimensions

Abstract: The extended Hubbard model with on-site interaction U and nearest-neighbor interaction V/d is studied at half filling in high dimensions (^^1). At small U and K the critical temperature and the order parameter are calculated including the \/d corrections. The results diifer from those obtained in the Hartree approximation by a factor of order unity. At K/t/ = l/2 a transition is found from an antiferromagnetic to a charge-density-wave phase. A similar transition is found at large U and K, suggesting that the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
100
1
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 19 publications
10
100
1
1
Order By: Relevance
“…As a result of the periodic boundary conditions on the cluster, this causes the near-neighbor fluctuations to be over estimated. As a result, the estimates of T N from these clusters, shown The dynamical mean-field approximation (DMFA, full circles), Staudt et al [7] (full curve), second order perturbation theory (SOPT, dotted curve) [10,11], the Heisenberg model (dashed curve) [12] and the Weiss mean-field theory for the Heisenberg model (dash-dotted curve). We took J = 4t 2 /U for both Heisenberg calculations.…”
mentioning
confidence: 99%
“…As a result of the periodic boundary conditions on the cluster, this causes the near-neighbor fluctuations to be over estimated. As a result, the estimates of T N from these clusters, shown The dynamical mean-field approximation (DMFA, full circles), Staudt et al [7] (full curve), second order perturbation theory (SOPT, dotted curve) [10,11], the Heisenberg model (dashed curve) [12] and the Weiss mean-field theory for the Heisenberg model (dash-dotted curve). We took J = 4t 2 /U for both Heisenberg calculations.…”
mentioning
confidence: 99%
“…Grabowski and Sham [7] carried out such an analysis for the interacting electron gas and found that vertex corrections strongly suppressed T c for plasma frequencies larger than ten percent of the fermi energy. Van Dongen [8] analyzed the Hubbard model (which can be viewed as the infinite-frequency limit of an electron-phonon model) and showed that quantum fluctuations (vertex corrections) reduced Hartree-Fock transition temperatures by more than a factor of three.…”
mentioning
confidence: 99%
“…In this limit many "direct" diagrams cancel against "exchange" diagrams (there is no interaction between electrons with the same spin) and the perturbation theory is easier to control. Quantum Monte Carlo simulations have already been performed [14], and weak-coupling expansions through second order (for transition temperatures) have also been investigated with different techniques [8,17]. Migdal's theorem states that, in the small-frequency limit, transition temperatures may be determined with a first-order approximation (using a dressed phonon propagator) because the vertex corrections vary as Ω/t * .…”
mentioning
confidence: 99%
See 2 more Smart Citations